2020
DOI: 10.4039/tce.2019.73
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metarhizium anisopliae (Clavicipitaceae) on Rhagoletis mendax (Diptera: Tephritidae) pupae and adults

Abstract: Blueberry maggot (Rhagoletis mendax Curran (Diptera: Tephritidae)) is a pest of blueberries (Vaccinium Linnaeus (Ericaceae)). Tephritid flies, including Rhagoletis Loew species, are susceptible to entomopathogenic fungi, but mortality levels depend on life stage targeted. We tested Metarhizium anisopliae (Metschnikoff) (Clavicipitaceae) strain S54 by application to pupae in the laboratory and using soil drenches in the laboratory and field. We hypothesised that younger (pre-diapause) pupae would be more suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Nithya and Rani (2019) reported that addition of a surfactant combination (polyethylene glycol, polyoxyethylene, glycerol, and tween-80) on three formulations (I: chitin enriched groundnut oil/CGNO + adjuvant combination/AC 1; II: -CGNO + AC 2; and III: CGNO + AC 3) are capable of improving L. lecanii biopesticide efficacy toward Bemisia tabaci, Amrasca biguttula, and Tetranychus sp. Similar studies on the surfactant addition into the oil formulation to enhance the effectiveness of entomopathogenic fungi have also been extensively reported (Oliveira et al 2018;Arnosti et al 2019;Renkema et al 2020).…”
Section: Surfactantsupporting
confidence: 54%
“…Nithya and Rani (2019) reported that addition of a surfactant combination (polyethylene glycol, polyoxyethylene, glycerol, and tween-80) on three formulations (I: chitin enriched groundnut oil/CGNO + adjuvant combination/AC 1; II: -CGNO + AC 2; and III: CGNO + AC 3) are capable of improving L. lecanii biopesticide efficacy toward Bemisia tabaci, Amrasca biguttula, and Tetranychus sp. Similar studies on the surfactant addition into the oil formulation to enhance the effectiveness of entomopathogenic fungi have also been extensively reported (Oliveira et al 2018;Arnosti et al 2019;Renkema et al 2020).…”
Section: Surfactantsupporting
confidence: 54%
“…A major hurdle to implementing botanical products for horticultural pest control is the uncertainty around how to effectively utilize volatile compounds in the field (e.g., volatilization rate, application method, and impact on infestation in small fruit) and economic feasibility. Of the few studies that have investigated essential oil deterrence in situ, methods for deploying the essential oils range from spray applications, wicking materials [40], polymer flakes [41] to intercropping with fragrant plant species [48,49]. Intercropping strawberries with peppermint plants that were periodically mowed to increase the amount of volatiles has been shown to actually increase the amount of SWD infestation in the fruit, potentially due to providing additional shaded habitat for SWDs during the day [49].…”
Section: Discussionmentioning
confidence: 99%
“…Of the few studies that have investigated essential oil deterrence in situ, methods for deploying the essential oils range from spray applications, wicking materials [40], polymer flakes [41] to intercropping with fragrant plant species [48,49]. Intercropping strawberries with peppermint plants that were periodically mowed to increase the amount of volatiles has been shown to actually increase the amount of SWD infestation in the fruit, potentially due to providing additional shaded habitat for SWDs during the day [49]. The greatest challenge to implementing an effective deterrent management tactic will be maintaining biologically relevant amounts of VOCs in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Both D. bivitattus and ICIPE 18 are native to Africa and, therefore, share a similar evolutionary history, while Z. cucurbitae is an alien pest of Asian origin, which could explain this discrepancy. Metarhizium anisopliae isolates were reported to caused a significant reduction in eclosion in other fruit fly species such as C. capitata, C. fasciventris, C. cosyra [26] and the blueberry maggot fly Rhagoletis mendax Curran [43]. When evaluated in cages under field conditions, a granular formulation of ICIPE 20 was found to reduce the eclosion of C. capitata, C. fasciventris and C. cosyra by 37-54%, and it would be interesting to investigate eclosion reduction in the most promising isolates against D. bivittatus under field conditions.…”
Section: Discussionmentioning
confidence: 99%